Lyric Experience in Poetry (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article analyzes and interprets the artistic quality of some selected poems by H. Akhmedova on the theme of love. Attention is also paid to the poet's poetic skills - the peculiarities of using artistic and figurative means, her ability to create unique sentences by appropriately using symbols, allegories, and metaphors, as well as her masterful use of landscape images to artistically reflect mental moods and situations.